PENDUGAAN KETERDAPATAN AKIFER AIRTANAH DENGAN METODE GEOLISTRIK DI KECAMATAN SUKATANI - KABUPATEN PURWAKARTA - Mohamad, Febriwan; Firmansyah, Yusi (Bulletin of Scientific Contribution, 2015)
The research area as administratively is located in Sukatani village, District Sukatani, Purwakarta, West Java Province. Based on the relief morphology, strato volcanic facies models and its lithology, geomorphology of Sukatani is strato volcanoes leg with radial drainage pattern. This area height of about 260-300 meters above sea level. Stratigraphy unit of research area is divided into two units, namely Tufic sandstones-Conglomerates, and Alluvium. The study is intended to determine the position and water resources at a certain depth below the surface and determine subsurface conditions. The study based on measurements of geoelectric method of geoelectric 1-D and 2-D configuration of Schlumberger. The results of study are in the form of rock resistivity values. They are interpreted in the cross-sectional shape and correlated with geological and hydrogeological conditions. Based on the resistivity value, distribution layer in the study area are classified into three packages, namely rock low resistivity layer (<35 ohm-meter) expected role as aquiclud layer, a layer of medium resistivity (35-100 ohm-meters) are expected to act as a layer aquifer, and a layer of high resistivity (> 100 ohm-meters) are expected to act as a layer aquifug.